(Dys)functional Aspects of Work Conditions. Example of Google - Wojtaszczyk, Katarzyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The paper presents the results of research conducted by literature studies. The aim of the research is the critical analysis of the work conditions. The research entity is Google company. This organization was chosen deliberately – the criterion of selection was the fact that Google is one of the most well-known employers in the world, with the most prestigious awards for employers.The discussion begins with the presentation of the tangible and intangible elements of the work environment and the characteristics of the research entity. The next section of the article analyzes the selected components of work conditions at Google. The last part of the paper focuses on the identification of the weaknesses of work conditions at Google.